Sequence specificity of in vivo reverse splicing of the Tetrahymena group I intron. - Roman, J (1999)
Reverse splicing of group I introns is proposed to be a mechanism by which intron sequences are transferred to new genes. Integration of the Tetrahymena intron into the Escherichia coli 23S rRNA via reverse splicing depends on base pairing between the guide sequence of the intron and the target site. To investigate the substrate specificity of reverse splicing, the wild-type and 18 mutant introns with different guide sequences were expressed in E. coli. Amplification of intron-rRNA junctions by RT-PCR revealed partial reverse splicing at 69 sites and complete integration at one novel site in the 23S rRNA. Reverse splicing was not observed at some potential target sites, whereas other regions of the 23S rRNA were more reactive than expected. The results indicate that the frequency of reverse splicing is modulated by the structure of the rRNA. The intron is spliced 10-fold less efficiently in E. coli from a novel integration site (U2074) in domain V of the 23S rRNA than from a site homologous to the natural splice junction of the Tetrahymena 26S rRNA, suggesting that the forward reaction is less favored at this site.